P100 Improving paediatrics' pressurised metered dose inhaler technique and asthma control: Inhaler verbal counselling vs. Trainhaler. (12th November 2015) - Ammari, WG; Al-Hyari, NK; Obeidat, N; Khater, M; Sabouba, A; Sanders, M
Abstract : Introduction: Verbal counselling (VC) is commonly used to train patients on correct inhaler technique. Patients forget the good inhaler use with time. Trainhaler (TH), Clement Clarke, UK, is a novel pressurised metered dose inhaler (MDI) training tool designed with feedback mechanisms to train patients coordinate releasing the aerosol with using a slow and deep inhalation flow (IF) through their MDI. Our aim was to compare VC with TH in children with asthma. Methods: Ethical approval was obtained and all children and their parents gave signed consent. At visit 1, asthmatic children, age 7–17 years, with an MDI hand-lung coordination problem including an IF >60 l/min were randomised into either the VC group that received verbal MDI training with emphasis on using a slow and deep IF; or into the TH group that were trained on- and given TH to practice at home. Children with correct MDI technique and IF ≤60 l/min formed the control group (CT). An 11-step MDI technique, peak IF through the inhaler and Asthma Control Questionnaire (ACQ) were evaluated. All subjects returned after 6 to 8 weeks (visit 2) for re-evaluation. Results: Thirty children took part. Table 1 presents the study outcomes. All VC and TH had correct MDI steps and slow IF post-training at visit 1. Unlike CT, Wilcoxon test showed a significant decrease (p < 0.01) in the incorrect MDI steps between visits 1 and 2, within VC and TH. Mann-Whitney test showed a significant difference (p < 0.01) in the incorrect MDI steps between the CT and both intervention groups at visit 1, but no significant difference (p > 0.05) was found at visit 2. Paired t-test showed significant reductions (p < 0.01) in IF and ACQ within TH. In VC, the ACQ improved at visit 2, but the IF did not. Conclusion: VC and TH improved the children's MDI technique which was reflected on better asthma control. VC children could not, however, maintain the acceptable IF through their MDI which is critical for aerosol lung deposition. An inhaler training tool available to patients at any time can be helpful.